The social and environmental importance of national parks in Brazil: a systematic review - Wagner, Carolina (2023)
The National Parks of Brazil are areas that have different functions, among them, to preserve the fauna and flora. Protected Areas (PAs) are essential tools for maintaining habitat integrity and the diversity of species that occur there. The present work seeks to highlight the importance of National Parks for the conservation of Brazilian biomes. In this way, it sought to contribute to the deepening of this theme by highlighting works that sought to know the importance and strategies of these environments, being a systematic bibliographical review research in the period from 2000 to 2022 in dissertations, articles, event annals, books, websites and book chapters, available in the databases: Scielo, Capes, Google Scholar and official websites. The results lead to the conclusion that the Conservation Units help to control deforestation and the uncontrolled exploitation of natural resources and that these surveys are important to fill gaps left by public policies. Therefore, knowing the different sectors of public power and civil society helps to control these bodies to invest in inspection actions and that studies like these can help in understanding the characteristics of each region, developing debates about the protection of nature.